KEMBALI KE SISTIM KURS TETAP (FIXED EXCHANGE RATE)? - Edy Rahmantyo Tarsilohadi (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2002)
Indonesia do want make the right Exchange Rate System, with be back to the Fixed Exchange Rate. In this paper, because of the economic condition and the environment monetary system, so the best system is still the Flexible Exchange Rate.